2015
DOI: 10.1007/s00709-015-0821-6
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective activities of curcumin and quercetin with potential relevance to mitochondrial dysfunction induced by oxaliplatin

Abstract: Peripheral neurotoxicity is one of the serious dose-limiting side effects of oxaliplatin (Oxa) when used in the treatment of malignant conditions. It is documented that it elicits major side effects specifically neurotoxicity due to oxidative stress forcing the patients to limit its clinical use in long-term treatment. Oxidative stress has been proven to be involved in Oxa-induced toxicity including neurotoxicity. The mitochondria have recently emerged as targets for anticancer drugs in various kinds of toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 95 publications
(108 reference statements)
3
77
0
Order By: Relevance
“…Wassem and Parvez showed that curcumin can ameliorate changes in both enzymatic and nonenzymatic antioxidants of mitochondria in vitro. The results reveal the potential of curcumin as a substance that can diminish oxaliplatin-induced peripheral neurotoxicity [98].…”
Section: Curcuminmentioning
confidence: 86%
See 1 more Smart Citation
“…Wassem and Parvez showed that curcumin can ameliorate changes in both enzymatic and nonenzymatic antioxidants of mitochondria in vitro. The results reveal the potential of curcumin as a substance that can diminish oxaliplatin-induced peripheral neurotoxicity [98].…”
Section: Curcuminmentioning
confidence: 86%
“…Moreover, c-Fos, a marker of neuroplasticity, was decreased by rutin-or quercetinpretreatment [25]. The neuroprotective mechanism of these phytochemicals is connected to its amelioration of mitochondrial dysfunction [98]. Interestingly, quercetin, but not rutin, inhibited azoxymethane-induced colorectal carcinogenesis in rats [101].…”
Section: Rutin and Quercetinmentioning
confidence: 99%
“…Mitochondria of brain frontal cortex of rat were isolated by the differential centrifugation method (Waseem and Parvez, 2016). Rats were decapitated and frontal cortex were dissected and homogenized by using a mechanically driven Teflon-fitted Potter-Elvehjem type homogenizer in ice-cold buffer A.…”
Section: Methodsmentioning
confidence: 99%
“…NADH dehydrogenase activity was assayed by spectrophotometrically according to Waseem and Parvez (2016). The enzyme activity was expressed as micromoles of NADH oxidized per minute per milligram protein using a molar extinction coefficient of 21,000 M −1  cm −1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation